ASPEK RELIGIUS NOVEL SEBELAS PATRIOT KARYA ANDREA HIRATA - Marwanto Marwanto (Balai Bahasa Kalimantan Barat, 2021)
This study aims to describe the religious aspect and examine the problem of how the religious aspect of Andrea Hirata's Eleven Patriot novel and its implementation as literary material in high school. Qualitative descriptive is used to describe religious aspects through religious beliefs, practices, experiences, knowledge, and consequences. This novel tells about patriotism and religious routine activities of Ikal. He is described as a child who is obedient to his parents, and even becomes an inspiration in determining his life and goals.